Implications of The Harmonization of Tax Regulations Law and Tax Incentives Related to Covid-19 - Isnaniati, Siti; Agustin, Beby Hilda; Aditya, Dafid Isha (Universitas Pamulang, 2023)
This study examines how the Law on Harmonization of Tax Regulations (HPP) related to taxation in connection with Covid 19 concerning tax obligations for VAT and PPS. The qualitative research uses a literature study method that conducts a critical and in-depth analysis of journals and articles related to the 2022 HPP Law, VAT, and Tax Amnesty (2018-2023). Based on research, it was found that despite the existence of VAT in the HPP Law, the provision of VAT incentives increased relatively high, amounting to IDR 38.43 trillion or grew 45.86 percent (Masitoh, 2022). The HPP Law also regulates a new tax program, the Voluntary Disclosure Program (PPS). The factor affecting the implementation of the 2022 tax PPS is to increase 2022 tax revenues starting from the State Budget, which has yet to reach the target due to the Covid-19 pandemic in 2020-2021.